Geographical assessment of algal productivity and water intensity across the United States - Quiroz, David, author; Quinn, Jason C., advisor; Marchese, Anthony, committee member; Reardon, Kenneth, committee member (Colorado State University. Libraries, 2021)
Water consumption due to evaporation in open algal cultivation systems represents a significant research gap in the resource assessment literature. Existing algal evaporation models often lack high spatiotemporal resolution or are not validated with experimental systems. This study presents a geographical and temporal assessment of the water requirements for commercial-scale production of algae biomass through a dynamic integrated thermal and biological modeling framework. Water demands were calculated through a validated dynamic thermal model which predicts temperature with an accuracy of -0.96 ± 2.72 °C and evaporation losses with a 1.46 ± 5.92 % annual accuracy. The biological model was validated with experimental data representing the current state of technology and shows an average error of -4.59 ± 8.13 %. The integrated thermal growth model was then utilized to simulate the water demands for biomass production of a 400-hectare algae farm at 198 different locations across the United States over a period of 21 years. Simulation outputs were used to determine algal protein yields, based on protein content, and fuel production via hydrothermal liquefaction. This foundation is integrated with life cycle methodology to determine the water footprint of algal biomass, proteins, and biofuels and to compare them to those of traditional energy crops and conventional fuels. Results indicate that less water-intensive cultivation can be achieved in the Gulf Coast region, where the average water footprints of the three simulated pathways were determined to be 155 m3 water tonne-1 biomass, 371 m3 water tonne-1 algal proteins, and 11 m3 GJ-1 biofuel. The water footprints of algal systems were found to be more favorable when compared to traditional biomass feedstocks such as soybeans and corn. However, when compared to petroleum-based fuels, results emphasize the need for more water-efficient strategies to reduce the water demands of algal cultivation. This work also incorporates a novel temperature tolerance assessment to identify the geographically specific temperature limits for algal strains in a commercial-scale facility. Results highlight the importance of high temporal and spatial resolution when modeling culture temperature, evaporative loss, and algae growth rate.